1994
DOI: 10.1111/j.1432-1033.1994.tb19935.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure determination of extracellular fragments of amyloid proteins involved in Alzheimer's disease and Dutch‐type hereditary cerebral haemorrhage with amyloidosis

Abstract: Amyloid deposition is a biochemical and histopathologic hallmark of various clinical forms of amyloidoses including Alzheimer's disease and the Dutch‐type hereditary cerebral haemorrhage with amyloidosis. The self‐aggregating peptides responsible for these irreversible deposits have been sequenced but the mechanisms involved in the aggregation processes are not well understood. In order to gain an understanding of the possible structures prior to self‐association, the extracellular fragment of the Alzheimer am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 35 publications
(46 reference statements)
3
39
0
Order By: Relevance
“…2B). NOEs were also observed between the aromatic side chains of Phe 19 and Phe 20 with the alkyl side chains of Val 18 , Ala 21 , and Val 24 ( Fig. 2C), indicating that these apolar side chains lie close together and form a hydrophobic cluster, which is at least partially populated.…”
Section: Structural Characterization Of A␤40 By Nmr At Low Ph-mentioning
confidence: 95%
See 3 more Smart Citations
“…2B). NOEs were also observed between the aromatic side chains of Phe 19 and Phe 20 with the alkyl side chains of Val 18 , Ala 21 , and Val 24 ( Fig. 2C), indicating that these apolar side chains lie close together and form a hydrophobic cluster, which is at least partially populated.…”
Section: Structural Characterization Of A␤40 By Nmr At Low Ph-mentioning
confidence: 95%
“…7) These two regions have a slight tendency to adopt extended backbone structures at pH 2.5 and 25°C as revealed by the conformational shifts and backbone NOE intensities in monomeric A␤. 8) A turn, residues 22-25, stabilized by a small hydrophobic cluster involving Val 24 , Ala 21 , Phe 20 , Phe 19 , and Val 18 , detected by NOEs in monomeric A␤, may form between these two hydrophobic regions. It should be borne in mind that the NMR data reported here correspond to the A␤ monomer.…”
Section: Dss Binds To the Central Hydrophobic Cluster Of Monomeric A␤mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanism of fibril formation is not known, in vitro studies [3,5,62] have shown that the Aβ-Q22 variant forms fibrils at a more accelerated rate than wild-type Aβ. This increased amyloidogenic tendency is probably due to a higher content of β-pleated sheet structure and a conformational change in the middle part of the molecule induced by the disappearance of the negatively charged Glu side-chain in the mutant peptide [9,45]. The presence of both allele products in the amyloid deposits suggest that the mutant peptide may induce a conformational change in the structure of the normal Aβ peptide.…”
Section: Aβ -Related Cerebral Amyloidosismentioning
confidence: 99%